UNDERGROUND INTERPRETATION OF POSSIBLE LANDSLIDE ZONE IN GERBOSARI VILLAGE, SAMIGALUH DISTRICT, KULONPROGO REGENCY USING GEOELECTRIC METHOD WITH DIPOLE-DIPOLE CONFIGURATION - Purnama Aditya; wibowo Nugroho Budi; Darmawan Denny (Prodi Fisika, Departemen Pendidikan Fisika, 2016)
The research aimed to identify the underlying structure of probable landslide zone in Gerbosari village, and toidentify the depth of slip plane according to resistivity value. This research was conducted using resistivity methodwith dipole-dipole configuration in Jetis subvillage, Jati subvillage and Dukuh subvillage, Gerbosari Village,Samigaluh District, Kulonprogo Regency. The main instrument used for data collecting is resistivitymeter NaniuraNRD 22 S. The scope area of the research was 1,1 x 0,5 km consisted of 3 lines of survey while the precise locationof the research lied at coordinate of 7⁰39’54,90” S to 7⁰40’20,94” S and 110⁰10’02,79 E to 110⁰10’17,00” E. Theresult of the measurement is processed using Res2dinv software that showed 2D layer. Geomorphologicalcharacteristics are dominated by clay, sandy clay, limestone and andesite rock. In the layer of line 1 at Jetissubvillage the resistivity value of slip plane is 147-489 Ωm with 7,19-8,50 meter of depth which is assumed aslayer of andesite. In the layer of line 2 at Jati subvillage the resistivity value of slip plane is 389-2171 Ω m with6,33-8,50 meter of depth which is predicted to be layer of limestone. In the third layer of line 3 at Dukuh subvillagethe resistivity value of slip plane is 315-1293 Ωm and interpreted as limestone, while the depth of the slip planehas not yet predicted.Keywords: Geoelectric, slip plane, landslide, Gerbosari